Gemeinsam für die Zukunft – Fridays For Future und Scientists For Future: Vom Stockholmer Schulstreik zur weltweiten Klimabewegung - Fopp, David; Axelsson, Isabelle; Tille, Loukina (transcript, 2021)
For the activists around Greta Thunberg and Fridays for Future, the ecological crisis is disturbing and therefore an occasion for a common social project: the new global climate movement is emerging. Science and research play a central role in this movement those in positions of political responsibility are called upon to "Listen to the Science". This refers not only to climate and environmental science, but also to its implications for economics, politics, philosophy and pedagogy. David Fopp describes the history of the united battle of Fridays for Future and Scientists for Future for a sustainable and just society from the internal perspective as an activist and scientist. As founder of Scientists for Future in Sweden and co-organiser of the global Week for Future, he provides insights into the origins and development of these movements and, in dialogue with the young strikers, presents perspectives and fields of action for a common future.